(untitled) (International journal of medical sciences, 2026)
Premature birth is the leading risk factor for neonatal mortality, accounting for 35% of the 3.1 million deaths annually. Worldwide, more than 15 million babies are born too early, too small, every year, which is equivalent to one baby being born prematurely every 116 minutes. Complications related to preterm birth are the leading cause of death in children under five years of age, with an estimated 900,000 global deaths in 2019. In our republic, the number of preterm births has increased by 15.4% in the last 3 years, with a total of 6,840 preterm births registered in 2019 and 10,873 in 2023, according to SIAT.